2019
DOI: 10.1017/s1479262119000157
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome assembly and polymorphism detection in Silene ciliata (Caryophyllaceae)

Abstract: Silene ciliata (Caryophyllaceae) is a key species to test evolutionary hypotheses in a global warming context. The recent advances in Next Generation Sequencing technologies can help in providing clues about climate-mediated local adaptation. In the present study, we analysed the full transcriptome of six individuals of S. ciliata from Central Spain, by aligning it with the transcriptome of S. latifolia. We aimed (a) to identify Single Nucleotide Polymorphisms (SNPs) in the transcriptome of the species, (b) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
(26 reference statements)
0
5
0
1
Order By: Relevance
“…Although common garden experiments such as this one only can demonstrate the existence of genetically based differentiation (not adaptation per se ), the information from other studies mentioned above provides additional evidence toward the conclusion that the phenological differentiation found here likely is the result of divergent selection (Giménez‐Benavides et al, 2011; Morente‐López et al, 2019; Sacristán‐Bajo et al, 2019). Alternatively, such differentiation could result from neutral processes unrelated to selection, such as genetic drift (Garcia‐Ramos & Kirkpatrick, 1997).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Although common garden experiments such as this one only can demonstrate the existence of genetically based differentiation (not adaptation per se ), the information from other studies mentioned above provides additional evidence toward the conclusion that the phenological differentiation found here likely is the result of divergent selection (Giménez‐Benavides et al, 2011; Morente‐López et al, 2019; Sacristán‐Bajo et al, 2019). Alternatively, such differentiation could result from neutral processes unrelated to selection, such as genetic drift (Garcia‐Ramos & Kirkpatrick, 1997).…”
Section: Discussionmentioning
confidence: 50%
“…The patterns of phenological differentiation found are also congruent with results obtained in subsequent experiments implemented with plants grown from seeds derived from the cuttings used in the present study (unpublished results). Moreover, a parallel transcriptomic study with the same populations identified SNPs (single nucleotide polymorphisms) with unusually high allele‐frequency differentiation between marginal and optimal environments, for candidate genes in the flower development pathway (Sacristán‐Bajo et al, 2019). In addition, the phenotypic differentiation found in this study adds to recent evidence of the adaptive potential of marginal populations at early life stages (i.e., seedlings).…”
Section: Discussionmentioning
confidence: 99%
“…selected for early flowering) (see also chapter 3). In this vein, a parallel transcriptomic study using material collected from the same study’s populations identified a set of candidate SNPs with unusually high allele frequency differentiation between marginal and optimal environments (Sacristán-Bajo et al, 2019). Many of these SNPs derived from candidate genes in the flower development pathway (Sacristán-Bajo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this vein, a parallel transcriptomic study using material collected from the same study’s populations identified a set of candidate SNPs with unusually high allele frequency differentiation between marginal and optimal environments (Sacristán-Bajo et al, 2019). Many of these SNPs derived from candidate genes in the flower development pathway (Sacristán-Bajo et al, 2019). Thus, these selection analysis and genomic approaches provide increased evidence that genetically-based phenological differentiation found in this study is the result of divergent selection between marginal and optimal populations.…”
Section: Discussionmentioning
confidence: 99%
“…En este sentido, en un estudio paralelo del transcriptoma (RNA-seq) realizado con las mismas poblaciones de S. ciliata se identificó un conjunto de genes candidatos con una diferenciación en la frecuencia de alelos (Single Nucleotide Polymorphisms, en adelante SNPs) inusualmente alta entre ambientes marginales y óptimos (Sacristán-Bajo et al 2019), lo que respalda la existencia de presiones selectivas de naturaleza ambiental. Muchos de estos genes candidatos están asociados con las rutas de desarrollo de la flor y procesos de respuesta al estrés abiótico (Sacristán-Bajo et al 2019). Algunos de estos genes han sido nuevamente identificados como candidatos a encontrarse bajo selección en un estudio de secuenciación masiva de ADN aplicando métodos de detección de variantes genéticas sujetas a selección y de estructura genética (Lara-Romero, datos sin publicar).…”
Section: Determinación Del Efecto De Las Presiones Selectivas Sobre Poblaciones Marginalesunclassified